Chuck. The complete third season [videorecording (Blu-Ray)] - McNeill, Robert Duncan, 1964-; Levi, Zachary, 1980-; Strahovski, Yvonne, 1982-; Gomez, Joshua, 1975- (Warner Home Video, 2010)
BuyMore Nerd Herd supervisor Chuck Bartowski unwittingly downloads national security secrets into his brain, and finds himself guarded by two federal agents as the world's most valuable intelligence asset.